Смородина и крыжовник - Поздняков Александр Дмитриевич (Библиотечка садовода-любителя, 1990)
Экземпляры: аб. (1991) / Инвентарный номер: 32958 / Цена: / Сис.шифр: 42.35 / Авт.знак: П 47 / ГРНТИ: 68.35.59 / ББК: 42.358